2016
DOI: 10.17533/udea.vitae.v23n3a05
|View full text |Cite
|
Sign up to set email alerts
|

COMPARISON AND VALIDATION OF a FAST METHOD FOR THE EXTRACTION AND QUANTIFICATION OF Α-Linolenic, EICOSAPENTAENOIC, AND DOCOSAHEXAENOIC FATTY ACIDS

Abstract: Background: Omega 3 family fatty acids are currently widely studied for the diverse effects they have on cardiovascular disease risk factors. Seafood is the main natural source of these compounds. Objetives: In this paper the accuracy is verified on the fat extraction in fish, between two methods, using one of the most employees as it is the Bligh & Dyer since 1959, compared with SOXTEC, one more updated method with more modern equipment and validated quantification method for some omega 3 fatty acids by gas c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 16 publications
1
1
0
Order By: Relevance
“…According to the FDA Reviewer Guidance for the Validation of Chromatographic Methods (1994), the acceptable value for each concentration should be less than 1% [27]. The good precision value indicated no variability in precision at different concentrations measured on the same and different days The study result was in line with a study by Oviedo Castrillon et al ( 2016) that found repeatability (RSD%) of less than 1%, in which n-3 PUFA (C18:3n-3, C20:5n-3 and C22:6n-3) were 0.6%, 0.5% and 0.1%, respectively, in a commercial tuna sample that was prepared in sextuplet and injected in triplicate [28]. In a study by Trbovic et al ( 2018), the reproducibility (RSD%) for majority n-3 PUFA (C18:3n-3, C20:5n-3 and C22:6n-3) in fish tissues were found to be less than 3%, a bit higher compared to this study [29].…”
Section: Precision (Repeatability and Intermediate Precision)supporting
confidence: 90%
See 1 more Smart Citation
“…According to the FDA Reviewer Guidance for the Validation of Chromatographic Methods (1994), the acceptable value for each concentration should be less than 1% [27]. The good precision value indicated no variability in precision at different concentrations measured on the same and different days The study result was in line with a study by Oviedo Castrillon et al ( 2016) that found repeatability (RSD%) of less than 1%, in which n-3 PUFA (C18:3n-3, C20:5n-3 and C22:6n-3) were 0.6%, 0.5% and 0.1%, respectively, in a commercial tuna sample that was prepared in sextuplet and injected in triplicate [28]. In a study by Trbovic et al ( 2018), the reproducibility (RSD%) for majority n-3 PUFA (C18:3n-3, C20:5n-3 and C22:6n-3) in fish tissues were found to be less than 3%, a bit higher compared to this study [29].…”
Section: Precision (Repeatability and Intermediate Precision)supporting
confidence: 90%
“…According to C. Truzzi et al (2017), the mean recovery FA fortified with low and high concentrations of FAME standard were 96 ± 9% (min-max, 81-115%) and 96 ± 7% (min-max, 81-111%), respectively, in an Antarctic fish muscle [26]. Meanwhile, the recovery (R%) of n-3 PUFA (C18:3n-3, C20:5n-3 and C22:6n-3) were 93.5%, 116.2% and 105.3%, respectively, as conducted by Oviedo Castrillon et al (2016) using a commercial tuna oil sample extracted using the Bligh and Dyer method [28]. Most of the R% in this study was comparable to our previous study that indicated satisfactory R% at about 90-120% in extracted fishes using the Bligh and Dyer method spiked with FA standard [33].…”
Section: Accuracymentioning
confidence: 69%